The implication of lean process Industry 4.0 on service company: motivation on marketer productivity enhancement - Adhie, Dhayawardhana; Wicaksono, Jemy; Syamil, Ahmad (Management and Entrepreneurship: Trends of Development, 2019)
Industry 4.0 is known as a continuous industrial revolution which has made rapid development through optimization processes supported by technological innovations since the end of the 1970’s. It has made the manufacturing industry become more productive with efficient operational costs through continuous technology information applications supported by the communication systems of futuristic technology. However, obstacles were often found in the early phases of the implementations, such as the low number of acquired accounts and average balances of new acquired customers in the months measured by marketers’ productivity in field. One of the factors that influenced the employee productivity level was motivation. Motivation is considered as a power that forces employees to reach specific goals and targets in organizations. This study aimed to determine the factors that influence working motivation in the financial service sector industry based on mobile banking applications. It also sought to find how far motivation influences employees’ working performance. A regression analysis approach was applied as method to find the effect of employee’s motivation on working performance by adding other variables. Then, the variable was analyzed whether it had a positive and significant correlation with the performance productivity variable. The result showed that there was a significant and positive correlation between motivation and marketers’ performance productivity. The other two variables gave a different response. Therefore, it can be concluded that industry differentiation on product, working pattern, and employee’s background were affecting the suitability result between employee’s motivation and produced performance level.JEL Classification: L1, M1, M21.